2020
DOI: 10.1111/jedm.12266
|View full text |Cite
|
Sign up to set email alerts
|

Studying Score Stability with a Harmonic Regression Family: A Comparison of Three Approaches to Adjustment of Examinee‐Specific Demographic Data

Abstract: For assessments that use different forms in different administrations, equating methods are applied to ensure comparability of scores over time. Ideally, a score scale is well maintained throughout the life of a testing program. In reality, instability of a score scale can result from a variety of causes, some are expected while others may be unforeseen. The situation is more challenging for assessments that assemble many different forms and deliver frequent administrations per year. Harmonic regression, a sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…In addition, we can consider using case weights to obtain a more generalized model that has a weighted distribution that is consistent with the target population distribution of test takers. See Lee and Haberman (2021) for an up-to-date study related to this topic. cases are dropped.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we can consider using case weights to obtain a more generalized model that has a weighted distribution that is consistent with the target population distribution of test takers. See Lee and Haberman (2021) for an up-to-date study related to this topic. cases are dropped.…”
Section: Discussionmentioning
confidence: 99%
“…One was that the test center information was available for each test taker and was accurate. The other consideration was that prior studies (Lee & Haberman, , ) had found regional effects on test taker performance.…”
Section: Methodsmentioning
confidence: 99%
“…One was that the test center information was available for each test taker and was accurate. The other consideration was that prior studies (Lee & Haberman, 2013, 2018) had found regional effects on test taker performance. Because 100 cluster-based groups were needed per test form, the average jackknife group sizes, N avg , should be approximately 46, 30, and 34 for Forms 1, 2, and 3, respectively (see section "Data Source" for the three sample sizes).…”
Section: Constructing 100 Cluster-based Groupsmentioning
confidence: 99%
See 2 more Smart Citations